Assessment of the Bacterial communities associated with Anopheles gambiae larval habitats in Southern Ghana - Akua Obeng Forson; Isaac Kwame Sraku; Idan Baah Banson; Jones Gyamfi; Kwabena Obeng Duedu; Yaw Asare Afrane (PLoS ONE, 2025)
Mosquito breeding habitats are ecosystems that comprise a complex, intimately associated micro-organism. This study aimed to determine the bacteria communities associated with Anopheles larval habitats and correlate their prevalence to the absence or presence of mosquito larvae. The 16S rRNA profiles of bacterial communities in Anopheles-positive breeding habitats (productive and semi-productive habitats) and negative habitats (non-productive) from Southern Ghana were analyzed using the Oxford Nanopore’s MinION platform with water and larval samples. A total of 15 bacterial taxa were identified across all habitats based on productivity. Significantly, mosquito-positive breeding habitats (productive and semi-productive) had more bacterial diversity compared to mosquito-negative habitats (non-productive). Comparison of the composition of bacteria in the different habitat types revealed that non-productive habitats had a higher prevalence of Epsilonproteobacteria (58.1%), while Gammaproteobacteria (33.2%) and Betaproteobacteria (30.5%) were dominant in the productive and semi-productive habitats. Gammaproteobacteria and Betaproteobacteria were the most abundant bacterial classes in Anopheles larvae. Comparing the water samples to larvae microbiomes revealed distinct composition. Betaproteobacteria (58.5%) and Cytophagia (10.7%) were predominately present in the water samples, whilst Betaproteobacteria (47.9%) and Gammaproteobacteria (21.6%) were dominant in the larval samples. This study revealed a higher bacterial composition may play a role in Anopheles mosquitoes’ attractiveness to a breeding habitat. These findings contribute to the understanding of which bacteria, directly or indirectly, can be linked to the absence or presence of mosquito larvae in breeding habitats and set the basis for the identification of specific bacterial taxa that could be harnessed for vector control in the future.